Primary sclerosing cholangitis and primary biliary cholangitis. Issue 10 (October 2022) - Perry, Michael; Pathak, Anjali
Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are rare and progressive cholestatic liver diseases that can result in end-stage liver disease. It is known that PSC and PBC patients have worse health outcomes compared with the general population. Both conditions share confusingly similar names, but do have significant differences in their epidemiology, aetiology, presentation, diagnosis, management and potential complications. This article aims to provide an overview of PSC and PBC for GPs.